Dreaming of The Peaceful Ways: An Evaluation of The Indonesian Deradicalisation Program - Taskarina, Leebarty; Nuri, Widiastuti Veronika (Technium Social Sciences Journal, 2021)
The Indonesian deradicalization program conducted by Indonesian National Counterterrorism Agency (BNPT) comes under public scrutiny due the number of terrorist recidivism with a total of 47 individuals during 2018 until 2020. This indicates that the ongoing deradicalization program has not been successful and effective and it requires a massive change across all levels. This article aims to analyse the Indonesian deradicalization programs which has been adopting the peacemaking criminology approach and how it is implemented. Employing a qualitative study through desk research and informal interviews as the data collection techniques, this article examines various problems and challenges that are hampering the peacemaking-based deradicalization programs in Indonesia, including the problem of database on the ex-convicts, methods of approach and assessment, reliance on the top-down approach conducted by government institutions, pandemic challenges, and inconsistencies with the legal or judicial aspects. Adapting to the social change approach by including the involvement of the non-government stakeholders is important for deradicalization program to work. This article recommends that the evaluation of deradicalization policies in Indonesia should consider the re-focusing of deradicalization goals by aiming at behavioural changes rather than mindset and ideological changes, incorporating gender aspects in deradicalization programs, research-based programs formulation based on intersecting multidiscipline research fields and the possibility for the deradicalization as well as disengagement privatization programs to increase the effectiveness and reduce inefficiency.